A bow‐tie model for analyzing explosion and fire accidents induced by unloading operation in petrochemical enterprises. Issue 1 (7th October 2018) - Chen, Mengmeng; Wang, Kai
Abstract : Explosion and fire accidents happen frequently in petrochemical enterprises. For improving risk management, Bow‐tie method is applied to analyze causes, consequences, and control methods of such disasters. Based on fault tree analysis, 42 combination scenarios of primary events leading to explosion and fire accident are achieved. Important order of primary events is determined. Event tree is developed where four consequences, with different occurrence probability and loss degree, are obtained considering of success or failure of emergency evacuation and automatic fire extinguishing system. Structure of Bow‐tie model is established where three accident sources, including limit concentration of liquefied petroleum gas, equipment fault or operation error and fire source, are taken into account. After identification of accident causes and consequences, precautionary and loss‐reducing measures are proposed. The model was applied to analyze explosion and fire accident occurring in Jinyu group of China, demonstrating poor connection between the pipe and oil tank truck and non‐explosion‐proof equipment resulted in the accident. The delayed emergency excavation and failure of automatic fire extinguishing system led to fully developed fire and heavy casualties. To reduce such disasters, controlling suggestions in terms of educational training, intelligent monitoring, equipment management, and safety management were provided for Jinyu group. © 2018 American Institute of Chemical Engineers Process Process Saf Prog 38: 78–86, 2019